Long‐term androgen deprivation, with or without radiotherapy, in locally advanced prostate cancer: updated results from a phase III randomised trial. (2nd March 2020) - Sargos, Paul; Mottet, Nicolas; Bellera, Carine; Richaud, Pierre
Abstract : Objectives: To report the long‐term oncological outcomes of a randomised trial comparing androgen‐deprivation therapy (ADT) combined with external beam radiation therapy (EBRT) and ADT alone in patients with locally advanced prostate cancer. Patients and Methods: In this multicentre phase III trial, patients were randomly assigned to ADT alone or ADT+EBRT. Leuprorelin 11.25 mg was administered for 3 years. The whole pelvis was treated at a dose of 46 Gy and the prostate with a boost from 20 to 28 Gy. The primary endpoint was progression‐free survival (PFS). Secondary endpoints included overall survival (OS), disease‐specific survival (DSS), locoregional PFS (LRPFS), metastasis‐free survival (MFS), biochemical PFS (BPFS), and tolerance. Results: With a median follow‐up of 7.3 years, 263 patients were included. The 8‐year PFS rate was significantly higher in the ADT+EBRT arm than in the ADT arm (48% vs 7%; hazard ratio [HR] 0.27, 95% confidence interval [CI] 0.17–0.39; P < 0.001); in patients with a baseline PSA level ≥50 ng/mL (HR 0.10, 95% CI 0.05–0.20; P < 0.001) and in patients with a baseline PSA level <50 ng/mL (HR 0.28, 95% CI 0.19–0.40; P < 0.001). The risk of death from prostate cancer was significantly reduced in the ADT+EBRT arm (sub‐HR [SHR] 0.48, 95% CI 0.25–0.91; P = 0.02). The 8‐year OS rate was 57% in the ADT arm and 65% in the ADT+EBRT arm (no significant difference). LRPFS was significantly in favour of the ADT+EBRT arm (SHR 0.61, 95% CI 0.42–0.89; P = 0.01). MFS was comparable between both arms ( P = 0.88). Analysis of toxicities revealed acute lower tolerance in the ADT+EBRT arm, with a gradual decrease in intensity from 6 months after the end of EBRT. Conclusions: These long‐term results confirm the oncological benefit of combining EBRT with ADT in the treatment of locally advanced prostate cancer.